Selective Activation of Tumor Necrosis Factor Receptor II Induces Antiinflammatory Responses and Alleviates Experimental Arthritis. Issue 5 (11th March 2018) - Fischer, Roman; Proske, Marcel; Duffey, Maëlle; Stangl, Hubert; Martinez, George F.; Peters, Nathalie; Kraske, Alexandra; Straub, Rainer H.; Bethea, John R.; Kontermann, Roland E.; Pfizenmaier, Klaus
Abstract : Objective: Treg cells modulate immune responses and can suppress the development of autoimmune diseases. Tumor necrosis factor receptor II (TNFRII) has been recognized as a key receptor on these cells that facilitates expansion and stabilization of CD4+ Treg cells. The purpose of the present study was to investigate the therapeutic activity of a novel TNFRII agonist in experimental arthritis as well as the role of different Treg cell subsets. Methods: A novel mouse TNFRII–selective fusion protein (EHD2‐sc‐mTNFR 2 ) was generated by genetic engineering. Mouse T cells were incubated together with interleukin‐2 and/or EHD2‐sc‐mTNFR 2, and the effects on Treg cells were analyzed by flow cytometry. Mice with collagen‐induced arthritis (CIA) were treated with EHD2‐sc‐mTNFR 2 or saline, and the therapeutic effects were monitored and characterized. Results: Selective activation of TNFRII was found to expand both CD4+ and CD8+ Treg cells. Moreover, TNFRII activation elevated the number of CD4+CD25+ and CD8+CD25+ Treg cells and increased the number of FoxP3‐expressing cells in CD8+, but not CD4+, Treg cells, indicating different mechanisms of TNFRII‐induced expansion of diverse T cell subsets with suppressive activity. In the CIA model, we demonstrated that administration of the TNFRII agonist EHD2‐sc‐mTNFR 2 led to the expansion of both CD4+ and CD8+ Treg cells in vivo and induced antiinflammatory responses that alleviated arthritis. Conclusion: Our findings support the use of TNFRII‐selective therapeutics as an effective approach to the treatment of arthritic disease and possibly other inflammatory and autoimmune diseases. Abstract : Video Abstract Video Abstract